Context-dependent autophagy in cancer: deciphering cytoprotective vs. cytotoxic roles and therapeutic modulation strategies - Samer Osama Kostandy; Salwa Aburageh Abuiessa; Mai Mostafa Helmy; Maged Wasfy Helmy (Advances in Medical, Pharmaceutical and Dental Research, 2025)
Autophagy is a highly conserved cellular process activated when cells are exposed to stress. It is responsible for maintaining cellular homeostasis by degrading and recycling the exhausted cell components. However, autophagy is considered a cell survival mechanism; recent studies revealed its dual role in cancer. Autophagy can act as cytoprotective in early tumor stages or cytotoxic in advanced malignancies. This review explores the underlying molecular mechanisms and key regulatory pathways of autophagy, such as mTOR, AMPK, and p53, and their roles in tumorigenesis. The contradictory nature of autophagy in cancer varies according to the cellular context and depends on genomic stability, metabolic adaptation, immune evasion, and therapy resistance. Additionally, this review discusses different therapeutic strategies targeting autophagy, including inhibitors such as hydroxychloroquine and inducers like rapamycin, which have shown promise in modulating autophagy for improved cancer treatment outcomes. The review also examines the role of autophagy in cancer stem cells, metastasis, and therapy resistance, providing insights into how autophagy modulation can enhance chemotherapy, radiotherapy, and immunotherapy. Given its context-dependent functions, a deeper understanding of autophagy’s intricate regulation is crucial for developing precision medicine approaches to effectively integrate autophagy-targeting strategies in cancer treatment. Received on, 05 March 2025 Accepted on, 18 March 2025 Published on, 15 April 2025